Liquefaction potential for the Kathmandu Valley, Nepal: a sensitivity study - Rama M. Pokhrel; Charlotte E. L. Gilder; Paul J. Vardanega; Flavia De Luca; Raffaele De Risi; Maximilian J. Werner; Anastasios Sextos (Bulletin of Earthquake Engineering, 2022)
An assessment of liquefaction potential for the Kathmandu Valley considering seasonal variability of the groundwater table has been conducted. To gain deeper understanding seven historical liquefaction records located adjacent to borehole datapoints (published in SAFER/GEO-591) were used to compare two methods for the estimation of liquefaction potential. Standard Penetration Test (SPT) blowcount data from 75 boreholes inform the new liquefaction potential maps. Various scenarios were modelled, i.e., seasonal variation of the groundwater table and peak ground acceleration. Ordinary kriging, implemented in ArcGIS, was used to prepare maps at urban scale. Liquefaction potential calculations using the methodology from (Sonmez, Environ Geol 44:862–871, 2003) provided a good match to the historical liquefaction records in the region. Seasonal variation of the groundwater table is shown to have a significant effect on the spatial distribution of calculated liquefaction potential across the valley. The less than anticipated liquefaction manifestations due to the Gorkha earthquake are possibly due to the seasonal water table level.